Exploring the Concept of Classical and Modern Tragedy in Peter Shaffer’s The Royal Hunt of the Sun and Equus - Azar Adil Miro (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The study of literary tragedy has become a broad literary subject since its inception in the theatre of Dionysus. However, tragedy as described by Aristotle is meant to achieve something; the result of tragedy leads to a cathartic state which is meant to purify one’s soul. The process of tragic feeling brings about purgation of soul. Modern tragedy cannot be compared with the classical tragedy in terms of achieving a common goal. Tragedy in the modern time places one’s soul in a state of perennial pain and eternal anguish of mind. Therefore, Peter Shaffer in his two selected plays, The Royal Hunt of the Sun and Equus, has used classical technique to explore a contemporary tragedy. The two selected plays reveal how men suffer in the modern world in a way that subjugates their souls into a depressed state. In The Royal Hunt of the Sun, men are made to suffer without deserving it. While in Equus, the psychological suffering becomes explicitly obvious. This study attempts to explore the elements of modern tragedy as they are reflected in the two texts. The thesis consists of seven main parts. The introduction overviews, the background of the study, it also explains the aim of the study, the significant of the study, research questions and the novelty of the study. The second chapter looks at the related studies about the topic. The third chapter consists of a textual analysis of The Royal Hunt of the Sun. Chapter four will be on the second drama play entitled Equus. The last part, the conclusion compares and overviews the whole study. The result reveals that modern tragedy is comprised of classical element of tragedy but with differences as a result of time changes. It also reveals that modern tragedy could be self-induced and it does not necessarily caused by fate as it is in classical tragedy.